2011
DOI: 10.3390/ijms12118181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyphenols on Oxidative Stress and Mitochondrial Dysfunction in Neuronal Death and Brain Edema in Cerebral Ischemia

Abstract: Polyphenols are natural substances with variable phenolic structures and are elevated in vegetables, fruits, grains, bark, roots, tea, and wine. There are over 8000 polyphenolic structures identified in plants, but edible plants contain only several hundred polyphenolic structures. In addition to their well-known antioxidant effects, select polyphenols also have insulin-potentiating, anti-inflammatory, anti-carcinogenic, anti-viral, anti-ulcer, and anti-apoptotic properties. One important consequence of ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 210 publications
(235 reference statements)
0
36
0
Order By: Relevance
“…Cerebral ischaemia and doxorubicin-induced vascular impairment involve mitochondrial damage [101,102] and preventing mitochondrial damage proved to be a successful novel treatment in these pathologies [103][104][105][106][107][108]. Since SIRT1 has been demonstrated to enhance or restore mitochondrial activity in various tissues [62,87,91,[109][110][111] it is logical to assume that the interference between PARP-2 and SIRT1 expression [62] could be key for the protective phenotype.…”
Section: Parp-2 In Oxidative Stress-related Diseasesmentioning
confidence: 99%
“…Cerebral ischaemia and doxorubicin-induced vascular impairment involve mitochondrial damage [101,102] and preventing mitochondrial damage proved to be a successful novel treatment in these pathologies [103][104][105][106][107][108]. Since SIRT1 has been demonstrated to enhance or restore mitochondrial activity in various tissues [62,87,91,[109][110][111] it is logical to assume that the interference between PARP-2 and SIRT1 expression [62] could be key for the protective phenotype.…”
Section: Parp-2 In Oxidative Stress-related Diseasesmentioning
confidence: 99%
“…Similarly, Prabhu and his colleagues (2012) inferred that treatment with MF significantly reduced the infarct area in a rat model. Cerebral edema is a major complication related to hypoxic-ischemia, as edema might elevate intracranial pressure with enlargement of brain tissue, which finally leads to cell death (Panickar & Anderson, 2011). It has been hypothesized that during HI condition, the blood flow was interrupted and contribute to an electrolytic imbalance that leads to increased movement of water (increases Aquaporin 4 expression) by altering BBB integrity and thus leads to edema (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical data indicated that 55-60% of infants with inborn HIE might suffer from severe disabilities such as epilepsy, mental retardation, cerebral palsy or even die (Kurinczuk et al, 2010;Long & Brandon, 2007). The etiology for HIE are associated with lack of oxygen supply to the brain by interrupting blood flow and finally leads to various metabolic derangements like an energy failure, excitotoxicity, oxidative stress (lipid peroxidation), inflammation, delayed cell death due to alteration in calcium homeostasis (Panickar & Anderson, 2011;Lai & Yang, 2010). Even though some treatment regimen are available for cerebral ischemia (HIE) such as anticonvulsants (antiepileptic), hypothermic treatments, and stem cell transplant, but none of them showed better results against HIE (Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Destruction of the mitochondrial energy metabolism is the immediate cause of mitochondrial dysfunction and disruption of oxidative phosphorylation a key mechanism of producing adenosine triphosphate (ATP) in cerebral ischemia [10,11]. The maintenance of the mitochondrial membrane potential (MMP), which helps to establish a proton gradient across the inner mitochondrial membrane to activate the adenosine triphosphate (ATP) synthase to generate high-energy phosphates, is disturbed during cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%